2007
DOI: 10.1007/s11274-006-9340-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion and biotransformation of coir pith for economic production of Pleurotus florida: chemical and biochemical changes in coir pith during the mushroom growth and fructification

Abstract: Coir pith represents~50% of the waste from the coir industries and was tested for its potential in serving as a growth substrate for the production of species of oyster mushroom, Pleurotus florida. Due to its high lignin (~48%) content and amorphous powdery nature, coir pith supported poor mushroom mycelial growth and yields were considerably low (~25% bioconversion efficiency). Pre-treating coir pith with hot water did not prove economical to produce the mushroom yields. Acid swelling and alkali delignificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…At the end of the cropping period, the substrate turned dark brown, with the production of Xuid that could possibly be due to the dissolution of lignin, as was reported by Wainright [32]. Cellulose and hemicellulose degradation pattern were similar to the results obtained with Pleurotus Xorida in a substrate formulated with a mixture of 80% of coir pith and 20% of rice straw [27]. It is important to state that, in our experiments, supplemented substrates showed higher decreases in cellulose, hemicelluloses and lignin content than S1 along the cultivation cycle.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…At the end of the cropping period, the substrate turned dark brown, with the production of Xuid that could possibly be due to the dissolution of lignin, as was reported by Wainright [32]. Cellulose and hemicellulose degradation pattern were similar to the results obtained with Pleurotus Xorida in a substrate formulated with a mixture of 80% of coir pith and 20% of rice straw [27]. It is important to state that, in our experiments, supplemented substrates showed higher decreases in cellulose, hemicelluloses and lignin content than S1 along the cultivation cycle.…”
Section: Discussionsupporting
confidence: 80%
“…White rot fungi such as P. tenuiculus can degrade lignin to reach other more readily available carbon sources present in the wood (cellulose and hemicellulose). Shashirekta and Rajarathnam [27] found higher lignin degradation in a period from incubation until the formation of pinheads, coinciding with a laccase peak activity. On the contrary, we found more lignin degradation during the fruiting state [27].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Chemical treatment of lignocellulosic material reduces its moisture absorption capacity and improves filler鈥搈atrix adhesion . Very few authors have reported the effect of chemical treatment on coir pith , but no study has focused on the effect of chemical treatment on coir pith鈥損olymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…. Cocopeat consists of 21-36% cellulose and 48-54% lignin (Israel et al 2011;Shashirekha and Rajarathnam 2007)…”
mentioning
confidence: 99%